IDENTIFIKASI KEBUTUHAN PERAWATAN MANDIRI IBU NIFAS - Imami Nur Rachmawati; Allenidekania Allenidekania; Maria A. Wijayarini (Jurnal Keperawatan Indonesia, 2001)
Tujuan penelitian ini adalah untuk mengidentifikasi kebutuhan perawatan nifas dan menggambarkan kepercayaan dan kebiasaan yang berhubungan dengan kesehatan pada nifas. Studi ini menggnakan desain deskriptif dengan dasar model Cox. Sampel sejumlah 100 ibu yang melahirkan di sebuah Puskesmas di Jakrta Pusat, sedangkan pemberi pelayanan kesehatan 15 orang. Data diperoleh melalui kuisioner dan wawancara berstruktur. Hasil analisa diperoleh bahwa ada kebutuhan yang kuat terhadap perawatan pada masa nifas. Komplikasi yang sering terjadi adalah pembengkakan payudara. Ibu nifas tidak memperoleh informasi yang adekuat tentang perawatan nifas. Kebiasan yang banyak dilakukan ibu nifas adalah tapelan untuk merawat otot perut dan rahim, pemijatan sekuruh tubuh pada saat tertentu sedangkan hubungan seksual sangat dilarang sebelum masa nifas berakhir. Terdapat keterbatasan sumber-sumber untuk pendidikan kesehatan di Puskesmas khususnya mengenai perawatan nifas. Dari penelitian ini dapat disimpulkan bahwa terdapat kebutuhan perawatan mandiri selama nifas dengan menggunakan pedoman yang tepat. Postpartum complications are significant factors that contribute to maternal death. The purpose of this research was to identify needs of postnatal care for postnatal women and to describe health beliefs and habits of the postnatal women. This was a descriptive study, using Cox model as a theoretical basis. The postnatal women, who have gave give birth in a community health center in Central Jakarta volunteered to be interviewed (n=100). Their caregivers (midwives and nurses) (n==15) were also interviewed to look for the existing postnatal program. Data from semi-structured questionnaires were analyzed with a descriptive approach. Analysis of the data revealed that: there are the strong needs for breast, abdominal and uterus and perineum care, elimination, nutrition, activity and exercise, and sexual activity. The most complication occurred during the postpartum period are breast engorgement. The respondent also perveived inadequate information to the mother regarding the postnatal care. The prominent self care beliefs and habits such as: ‘tapelan’ –traditional cares for the abdomen following their delivery is widely used; massaging the whole body; and the sexual intercourse is indeed prohibited during the postpartum period. There are limited resources of health education material in the Community Health Center, as well as limited health education program regarding the postnatal care. The findings showed strong implication for nursing practice and education. It was concluded that there are strong needs of postnatal self-care with the health guidance. Also there is a strong desire for the postnatal women to get health teaching about self-care during the postpartum period along with written information. A replication of this study, or the initiation of a similar large study, would greatly increase the potential to generalize of the findings.